1999
DOI: 10.1126/science.283.5408.1724
|View full text |Cite
|
Sign up to set email alerts
|

Single-Polymer Dynamics in Steady Shear Flow

Abstract: The conformational dynamics of individual, flexible polymers in steady shear flow were directly observed by the use of video fluorescence microscopy. The probability distribution for the molecular extension was determined as a function of shear rate, ␥, for two different polymer relaxation times, . In contrast to the behavior in pure elongational flow, the average polymer extension in shear flow does not display a sharp coil-stretch transition. Large, aperiodic temporal fluctuations were observed, consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
836
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 723 publications
(902 citation statements)
references
References 26 publications
53
836
3
Order By: Relevance
“…It was found that, at relatively high shear rates, the sharp coil-stretch transitions of DNA chains observed in pure elongation flow was absent in shear flow. 16,21 Individual chains in steady shear flow rather showed large, aperiodic temporal fluctuations in conformation, consistent with what had been predicted in theory. 84 In addition, stretching of DNA chains in shear flow occurred at a strain value \50 (%10 1 ), 16 which is several orders of magnitude lower than the %10 5 critical strain value observed for poly-L-lysine 55 as well as folded proteins.…”
Section: Molecular Models and Theoretical Aspectssupporting
confidence: 87%
See 3 more Smart Citations
“…It was found that, at relatively high shear rates, the sharp coil-stretch transitions of DNA chains observed in pure elongation flow was absent in shear flow. 16,21 Individual chains in steady shear flow rather showed large, aperiodic temporal fluctuations in conformation, consistent with what had been predicted in theory. 84 In addition, stretching of DNA chains in shear flow occurred at a strain value \50 (%10 1 ), 16 which is several orders of magnitude lower than the %10 5 critical strain value observed for poly-L-lysine 55 as well as folded proteins.…”
Section: Molecular Models and Theoretical Aspectssupporting
confidence: 87%
“…It is modeled as a linear superposition of rotational flow with vorticity x, and elongational flow with strain rate _ c ¼ @v x @y . 16 In the rotational component of the flow field, protein molecules experience whole body rotation with no hydrodynamic shear strain, hence maintain their structural integrity. However, protein molecules are subjected to stretching events when oriented in the extensional flow field.…”
Section: Studying the Effect Of Shear Flow On Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether shear alone or an initial extensional flow event prior to shear is required to induce WFL aggregation remains to be seen. The latter scenario could cause a localized unfolding of a protein molecule (e.g., as seen for von Willebrand factor (Lippok et al, 2016) and for BSA in our previous study (Dobson et al, 2017), which may then be susceptible to “tumbling” events under shear flow in the capillary (Smith, Babcock, & Chu, 1999) and rapid self‐association in a concentration and time‐dependent manner.…”
Section: Discussionmentioning
confidence: 77%